Box-Behnken Modeling Served for the Development and Optimization of Nanoparticles Loaded with Perindopril and Erbumine - Malviya, Vedanshu (Asian Journal of Pharmaceutics (AJP), 2023)
Background: The study aimed to optimize and validate a nano-particulate technology for the sustained release of perindopril erbumine, an angiotensin-converting enzyme (ACE) inhibitor, using a box-behnken experimental methodology. Methods: The researcher used a Box-behnken experimental methodology to optimize the formulation and assess various characteristics such as particle size, zeta potential, surface shape, encapsulation efficiency and in vitro drug release. The nanoparticles characterization findings were recorded included the size, polydispersity index, zeta potential and encapsulation efficiency. Results: The nanoparticles had a smooth surface and their size was determined to be 122.38 ± 0.75 nm. The polydispersity index was 0.298, the zeta potential was 38.79 ± 0.05 mv and the encapsulation efficiency was 61.73 ± 0.06%. In vitro release was restricted for up to two hours, but at a pH of 7.4, the rate of drug release increased and was maintained. Conclusion: The study concluded that the nano-particulate technology for the potential to improve therapeutic efficacy and decrease dosage frequency for drug that need repeated doses such as perindopril erbumine.